On the purpose of meaningful human control of AI - Davidovic, Jovana (Frontiers in Big Data, 2023)
Meaningful human control over AI is exalted as a key tool for assuring safety, dignity, and responsibility for AI and automated decision-systems. It is a central topic especially in fields that deal with the use of AI for decisions that could cause significant harm, like AI-enabled weapons systems. This paper argues that discussions regarding meaningful human control commonly fail to identify the purpose behind the call for meaningful human control and that stating that purpose is a necessary step in deciding how best to institutionalize meaningful human control over AI. The paper identifies 5 common purposes for human control and sketches how different purpose translate into different institutional design.